The Role of Counterfactual Thinking on Attitudes Toward ADHD Medication Use. (20th March 2016) - Ramos, Ashley M.; Becker, Brittney; Biemer, Julie A.; Clark, Lindsay; Fields, Sherecce; Smallman, Rachel
ABSTRACT: Objective : Despite serious health risks, attitudes toward Attention-Deficit Hyperactivity Disorder (ADHD) medication use in college students remain favorable. Given the robust link between attitudes and behavior (e.g., the Theory of Planned Behavior), it is important to understand how these attitudes are developed and maintained. The current study examined the role of counterfactual, or "what if'" thinking as a mechanism for the development of attitudes toward ADHD medications. Method : All participants ( n = 190) were asked to read either a positive or negative scenario regarding ADHD medication misuse and rate their attitudes toward the behavior; half of the participants were also asked to generate counterfactuals prior to rating their attitudes. Results : Results suggest that scenario valence influenced the direction of counterfactual statements. Further, through the generation of upward counterfactuals, the negative scenario elicited more positive attitudes toward ADHD medication misuse. Conclusions : Based on limited prior research, it is suggested that upward counterfactuals may allow individuals to explain away the misuse of ADHD medication and avoid negative emotions such as guilt and shame related to current or prior ADHD medication misuse. In sum, additional research is needed to confirm preliminary findings that suggest counterfactual thinking could be a precursor to ADHD medication misuse.